Rice Tolerance to Flooding Stress on Germination Stage and Early Seedling Growth under 5 cm Water Depth - Arinal Haq Izzawati Nurrahma; Ahmad Junaedi; Heni Purnamawati (AGRO SINTESA JURNAL ILMU BUDIDAYA PERTANIAN, 2019)
Flood is one of the major environmental constraints that may harm plant productivity which requires specific mechanism to cope with stress. Flood prone area where rice is major crop to be cultivated, transplanting method on cultivation system cost high labor with consequence on low seedling survival. Direct seeding may offer solution for this condition with additional improvement needed on seed tolerant to germinate on anaerobic environment. An experiment was conducted to evaluate 23 rice varieties of tolerance to flooding stress on germination stage under 5 cm water depth. The experiment design was Nested – Randomized Complete Block Design with two factor and three replications. Result showed that rice germination under anaerobic condition was varied with Lambur has highest survival rates among others. Tolerance level was characterized from higher survival ability followed by high biomass accumulation and length of the shoot and root.Keywords: anaerobic germination, direct seeding